From Physical to Spiritual Errand: The Immigrant Experience in John Winthrop, William Bradford, and Samuel Danforth - Fruzińska, Justyna (Text Matters: A Journal of Literature, Theory and Culture, 2015)
The paper analyzes early colonial representations of the New World, connected with immigration of the first- and second-generation religious dissenters in what was to become America. Taking into account the well-documented influence of Puritans on American identity (often noticed by scholars since Tocqueville), the paper elaborates on the Puritans’ and Pilgrims’ mindsets as they arrived in the New World, connected not only with their religious beliefs but most of all with a practical need to organize themselves effectively. Be it in John Winthrop’s “A Modell of Christian Charity,” William Bradford’s “Of Plymouth Plantation” or Samuel Danforth’s “New England’s Errand into the Wilderness,” the authors of these works clearly show how the Pilgrims and Puritans had to confront the experience of emigration/immigration and construct not only new ways of social organization but also new identity. The paper focuses on the immigrants’ perception of the New World, their own role and challenges they were faced with, and their thinking about the society they came from and were about to construct. It deals with their process of adjusting to the surroundings and discussing values they decided to promote for the sake of communal survival in the adverse conditions of the New World.